Deficiency and toxicity of nanomolar copper in low irradiance-A physiological and metalloproteomic study in the aquatic plant Ceratophyllum demersum - Thomas, George; Andresen, Elisa; Mattusch, Jürgen; Hubáček, Tomáš; Küpper, Hendrik (Aquatic toxicology, 2016)
Essential trace elements (Cu(2+), Zn(2+), etc) lead to toxic effects above a certain threshold, which is a major environmental problem in many areas of the world. Here, environmentally relevant sub-micromolar concentrations of Cu(2+) and simulations of natural light and temperature cycles were applied to the aquatic macrophyte Ceratophyllum demersum a s a model for plant shoots. In this low irradiance study resembling non-summer conditions, growth was optimal in the range 7.5-35nM Cu, while PSII activity (Fv/Fm) was maximal around 7.5nM Cu. Damage to the light harvesting complex of photosystem II (LHCII) was the first target of Cu toxicity (>50nM Cu) where Cu replaced Mg in the LHCII-trimers. This was associated with a subsequent decrease of Chl a as well as heat dissipation (NPQ). The growth rate was decreased from the first week of Cu deficiency. Plastocyanin malfunction due to the lack of Cu that is needed for its active centre was the likely cause of diminished electron flow through PSII (ΦPSII). The pigment decrease added to the damage in the photosynthetic light reactions. These mechanisms ultimately resulted in decrease of starch and oxygen production.
Keywords: proteom; proteomika; Copper; Biomarkers; vodní organismy; chemické látky znečišťující vodu; Light; Aquatic Organisms; Toxicity Tests; biologické markery; Photosynthesis; Magnoliopsida; Proteomics; měď; testy toxicity; fotosyntéza; Proteome; Water Pollutants, Chemical; světlo